FENOMENA HASHTAG SEBAGAI ALTERNATIF PENCARIAN INFORMASI DALAM PERILAKU BERSOSIAL MEDIA - I Made Indra Wirayuda (D3 Perpustakaan FISIP UNUD, 2024)
Searching for information on the internet, especially social media, using hashtags is certainly something that is no longer foreign in today's digital era. The role of hashtags as an alternative for searching for information that is quite easy to use can be utilized by all levels of society. Freedom of communication on social media has resulted in the use of hashtags being used frequently as a tool to expand the reach of information dissemination. This article explains how hashtags play a role in the behaviour of internet users in searching for information on the internet. There are many benefits to using hashtags on social media, such as helping to find relevant information, helping to advertise products, and being used as a tool to voice opinions by activists, both individually and publicly. The use of hashtags can also have a negative impact, as caused by social media users lacking ethics in communicating in the internet environment. Hashtags can be ranked based on the number of social media users who use the same hashtag, so that hashtags become one of the benchmarks for how information can be declared as viral or popular information.